Vitiligo treatment: a literature review - Leżanko, Monika J.; Pyrek, Adrianna P.; Placek, Waldemar; Owczarczyk-Saczonek, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2024)
Vitiligo is a chronic disease characterized by the focal damage of melanocytes, which results in formation of discoloured spots on the skin. This disease affects from 0.5% to even 4% of the general population and the first symptoms appear before the patient reaches the age of 30 in majority of cases. The pathogenesis involves genetic and immunological factors, adhesion of melanocytes to the epithelium, as well as metabolic factors related to cellular oxidative stress. Many methods are used in treatment, including pharmacology, surgery or phototherapy. In our review, we have included either the treatment methods for vitiligo that have been used for years, or new, promising methods that could become the leading treatments for this condition in the future.